Uso do ambiente e plasticidade alimentar da pescada branca (Plagioscion Squamosissimus, Heckel, 18400), capturada na porção interna do estuário amazônico - MESQUITA, Esther Mirian Cardoso (2019)
This study aimed to characterize the use of the environment and feeding plasticity of pescada branca (Plagioscion squamosissimus, Heckel, 1840), captured in the inner portion of the Amazon estuary (Pará river, Guajará Bay and Marajó Bay). We used data collected in the period 2006 to 2010, using gill nets with mesh sizes (channels) and Hurdle (streams). The samples were taken considering the stations of the region (rainy, rainy-dry transition, dry and dry-rainy transition). We collected 1710 individuals in total, this total 495 were for Marajó Bay, 847 Guajará Bay and 368 in to Pará river. Were analyzed the repletion index (RI) and stomach fullness (GR) as well as analysis stomach contents, which was estimated Frequency of Occurrence (% FO), Numerical Frequency (% N) and Percentage Weight (% P). Were considered to analysis the area, period, maturation (juvenile and adult) and environment (channel and stream). The variations were tested by analysis of variance (ANOVA). The results showed that the all areas analyzed were used to feed P. squamosissimus, since more than half of the stomachs analyzed had food. The rainy season shoed the highest numbers of individuals with stomachs full, feeding on the Pará River and Guajará Bay. The streams were intensive environments feeding activity when compared to the channel, due to greater food availability in these areas. The principal area of feeding of the juveniles individuals was the Guajará Bay and the adults in the others two areas. The crustaceans were dominant in the diet with emphasis on Macrobrachium amazonicum and Acetes paraguayensis, followed by teleosts. In the Para River the diet of P. squamosissimus was composed mainly of A. paraguayensis while in Guajará Bay there is the domain of M. amazonicum. In the Marajo Bay teleosts are the main item of diet. This variation is related to the size of individuals captured and trophic plasticity of pescada branca. No significant differences in diet composition when considering the period of the year. In the channel was predominantly teleosts. And, in the streams of crustaceans. Wasn‟t observed significant differences between juveniles and adults as the composition of the diet. P. squamosissimus has a carnivorous habit with tendency to piscivory, however, this work proved to be opportunistic consuming the item that was available in the environment.